TMCO1 regulates cell proliferation, metastasis and EMT signaling through CALR, promoting ovarian cancer progression and cisplatin resistance: TMCO1 promotes ovarian cancer and cisplatin resistance - Sun, Guangyu; Gong, Shan; Lan, Suwei; He, Ying; Sun, Yanhua; Zhang, Zhengmao (Cellular and Molecular Biology, 2024)
This study aimed to explore the involvement of Transmembrane and coiled-coil domains 1 (TMCO1) in ovarian cancer progression and its regulatory mechanisms in cisplatin resistance. Using the GEPIA database, we analyzed TMCO1 expression in ovarian cancer and normal tissues. In a cohort of 99 ovarian cancer patients, immunohistochemistry and immunofluorescence were employed to assess TMCO1 expression in tumor and adjacent tissues, correlating findings with clinical and pathological characteristics. TMCO1 overexpression and knockout cell models were constructed, and their impact on non-cisplatin-resistant (SK-OV-3) and cisplatin-resistant (SK-OV-3-CDDP) ovarian cancer cells was investigated through cloning, wound healing, Fluo 4, and Transwell experiments. Knocking down CALR and VDAC1 was performed to examine their effects on TMCO1, cell proliferation, and malignant markers. Subcutaneous tumor models in nude mice elucidated the in vivo role of TMCO1 in tumor growth. Expression levels of CALR, VDAC1, angiogenesis indicators (CD34), and epithelial-mesenchymal transition (EMT) markers were evaluated. TMCO1 expression in ovarian cancer tissue significantly differed from normal tissue, correlating with survival rates. TMCO1 overexpression was associated with lymph node metastases, late FIGO stage, and larger tumors. TMCO1 promoted proliferation, calcium ion elevation, cytoskeletal remodeling, and metastasis in SK-OV-3 and SK-OV-3-CDDP cells, upregulating VDAC1, CALR, Vimentin, N-cadherin, β-catenin, and downregulating E-cadherin. Silencing TMCO1 inhibited cell growth, proliferation, and angiogenesis in vivo, suppressing the expression of CALR, VDAC1, Vimentin, N-cadherin, and β-catenin. Overall, this study highlighted TMCO1 as a crucial regulator in ovarian cancer progression, influencing VDAC1 through CALR and impacting diverse cellular processes, offering potential as a targeted therapeutic strategy for ovarian cancer.